Antimicrobial resistance: a growing threat in clinical practice (Journal of Armed Forces Medical College, Bangladesh, 2015)
Abstract not available DOI: http://dx.doi.org/10.3329/jafmc.v9i2.21817 Journal of Armed Forces Medical College Bangladesh Vol.9(2) 2013